Cognitive and Pedagogical Impacts of Introducing English in Elementary Schools in Francophone African Contexts: The Challenge of Local Language Dominance - (:unkn) unknown (My University, 2024)
This research examines the challenges and opportunities of introducing English as a third language in multilingual francophone African educational systems. The study analyzes existing literature and empirical data on the cognitive, pedagogical, and sociocultural impacts of trilingualism in educational contexts. The findings reveal significant challenges, including cognitive overload among learners and the need to adapt traditional teaching methods. However, the study also demonstrates that trilingual learning, supported by inclusive language policies and tailored pedagogical approaches, can promote cognitive development and the socioeconomic integration of learners. These results highlight the importance of a holistic approach that integrates local languages while preparing students for the demands of a globalized world.
Keywords: African Research